2002
DOI: 10.1017/s0022029901005325
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of electromyographic pattern of sensory experts and untrained subjects during chewing of Mahon cheese

Abstract: Use of electromyography (EMG) to monitor mastication is a relatively new concept in assessing food physical and sensory properties. Although expert assessment of cheese characteristics is widely used, the effect of training in sensory analysis on mastication patterns, as assessed using EMG is not well known. Nine samples of the same Mahon cheese (60 days ripening) were given to 24 subjects (8 experts, 16 untrained) and EMG recorded for each chewing sequence. Three samples were tested in a single session by eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
(62 reference statements)
1
18
0
Order By: Relevance
“…It is worth noticing that such an increase in performance through practice is possible as long as there is potential for the perceptual variance to decrease through factors such as attention, concentration and familiarity with the testing procedure. Studies involving texture have shown for instance that trained panelists have more constant chewing patterns than untrained subjects across samples and sessions (Gonzàlez, Sifre, Benedito, & Noguès, 2002;Mioche & Martin, 1998). However, if the main source of variability comes from the stimulus itself, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noticing that such an increase in performance through practice is possible as long as there is potential for the perceptual variance to decrease through factors such as attention, concentration and familiarity with the testing procedure. Studies involving texture have shown for instance that trained panelists have more constant chewing patterns than untrained subjects across samples and sessions (Gonzàlez, Sifre, Benedito, & Noguès, 2002;Mioche & Martin, 1998). However, if the main source of variability comes from the stimulus itself, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The types were independent of the agar samples (Table 2). Several previous studies have analysed conventional physiological parameters, such as chewing time and number of chewing cycles [1][2][3][4][5][6], and documented some differences in chewing performance among individuals. For example, in one of the studies [3], the authors classified their subjects into five sub-groups based mainly on chewing time and the muscle work rate during chewing.…”
Section: Discussionmentioning
confidence: 99%
“…Because few previous studies have used specific parameters, such as T 50 or D 50 values, to study the activity patterns of the masticatory muscles, the present study is likely to be the first report of the classification of subjects defined by specific parameters. In future experiments, both males and females should participate as subjects because there have been positive [6] and negative [4] findings concerning sex differences in chewing behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations